2022
DOI: 10.1021/jacs.2c11664
|View full text |Cite
|
Sign up to set email alerts
|

Uncanonical Semireduction of Quinolines and Isoquinolines via Regioselective HAT-Promoted Hydrosilylation

Abstract: Heterocycles are the backbone of modern medical chemistry and drug development. The derivatization of “an olefin” inside aromatic rings represents an ideal approach to access functionalized saturated heterocycles from abundant aromatic building blocks. Here, we report an operationally simple, efficient, and practical method to selectively access hydrosilylated and reduced N-heterocycles from bicyclic aromatics via a key diradical intermediate. This approach is expected to facilitate complex heterocycle functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…In 2023, Qin and co-workers reported a method for selective hydrosilylation or reduction on the phenyl site of (iso)quinolines ( Scheme 6 ). 34 The regioselectivity of the hydrosilylation reaction is substrate- and substituent-dependent, possibly due to the more electron-deficient radicals being photochemically generated at the 5-position of quinoline or 8-position of isoquinoline. The arenes of fused heterocyclic (iso)quinolines and quinazolines were selectively dearomatized.…”
Section: Photochemical Dearomative Functionalization Of Heteroaromaticsmentioning
confidence: 99%
“…In 2023, Qin and co-workers reported a method for selective hydrosilylation or reduction on the phenyl site of (iso)quinolines ( Scheme 6 ). 34 The regioselectivity of the hydrosilylation reaction is substrate- and substituent-dependent, possibly due to the more electron-deficient radicals being photochemically generated at the 5-position of quinoline or 8-position of isoquinoline. The arenes of fused heterocyclic (iso)quinolines and quinazolines were selectively dearomatized.…”
Section: Photochemical Dearomative Functionalization Of Heteroaromaticsmentioning
confidence: 99%
“…Remarkably, Dai and Curran [72] demonstrated that recoverable semiconductor ultrathin cadmium sulfide (CdS) nanosheets are also capable of enabling the photochemical hydroborylation of benzenoid arenes. Later, direct UV irradiation is introduced by Qin et al [27] . by presenting an elegant hydrosilylation of heteroaromatics (Scheme 29).…”
Section: Hydroamination Borylation and Silylation Of Benzenoid Arenesmentioning
confidence: 99%
“…Remarkably, Dai and Curran [72] demonstrated that recoverable semiconductor ultrathin cadmium sulfide (CdS) nanosheets are also capable of enabling the photochemical hydroborylation of benzenoid arenes. Later, direct UV irradiation is introduced by Qin et al [27] by presenting an elegant hydrosilylation of heteroaromatics (Scheme 29). As proposed by the authors, substrate 114 is excited by UV light irradiation in the presence of hexafluoro-2-propanol (HFIP) to form the excited-state intermediate 114-I, and the following hydrogen atom abstraction from silane yields 114-II and the radical R 3 Si * .…”
Section: Hydroamination Borylation and Silylation Of Benzenoid Arenesmentioning
confidence: 99%
“…Although the photo-triggered sequential-transformation strategy provides an elegant synthetic platform for arene dihydrogenation, the photoinduced direct reduction approach is more advantageous in terms of step economy and has witnessed significant progresses. For example, Qin et al [27] reported an elegant UV-induced dihydrogenation for bicyclic heteroaromatics, in which the reduction was generally occurring on the benzenoid ring (Scheme 7). Remarkably, this synthetic platform demonstrated excellent functional group tolerance as well as good yields.…”
Section: Photochemical Approachmentioning
confidence: 99%